Opportunities and applications of dendrochronology in Africa - Gebrekirstos, Aster; Bräuning, A.; Sass-Klassen, U.; Mbow C (Elsevier, 2014)
Partly due to severe lack of instrumental climate data, the drivers of the African climate, their interactions and impacts are poorly understood. The paper demonstrates the prospects and applications of dendroecological and stable isotope techniques, such as to reconstruct climate variability, trends and atmospheric circulation patterns, to fill the knowledge gap in ecosystem productivity and hydrological cycle in different climatic zones of Africa. We summarize the contribution of tree-ring analyses to validation of climate and hydrological models for improved scenarios, and to identify agroforestry species with the ability to acclimate to exacerbated climate conditions. A high number of African tree species shows datable annual tree rings and may reach multi century age. To advance dendrochronology in Africa, collaborative efforts in capacity building of African universities and research organizations are needed.